REASON FOR PRIVATE COMPANY MEMBER EXPULSION BASED ON COURT DECISION - Šogorov, Stevan (Zbornik radova Pravnog fakulteta u Novom Sadu, 2012)
In Serbian post war law expulsion of private company member was regulated in same manner regardless of grounds for expulsion. According to 2011 Company Act there are two different procedures – one for expulsion based on members meeting decision because of non performance of contribution and other grounded on court decision for other reason. Second group of reasons are discussed in this article. Private company can sue for expulsion of member only if the reason for expulsion is stipulated in memorandum of association or if it is justified. Reasons declared as justified by the Act can not be examined by court.